Gauge theory of pairing and spin fluctuations near the quantum critical point and superhigh-temperature superconductivity: Spin Models - Schrieffer, J.R. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
We develop a new theory of pairing and magnetic effect near the quantum critical point. Severalnovel properties are predicted: based on a spin fermion model, we derive two new interactions, i) a spin deformational potential Hsdp proportional to the bandwidth W (as opposed to the considerably smaller exchange coupling J of the nearly antiferromagnetic Fermi liquid theory) and ii) a diamagnetic potential Hdia, quadratic in a gauge potential A. A dramatic increase of Tc is predicted for 0.01 W ≤ J ≤ 10W. This should have immense technological impact in electric energy production, storage and transmission, as well as for medical electronics, microwave electronics, computer memory and information storage, separations technology and maglev, amongst others. The striking prediction to be confirmed by experiment is that the pairing order parameter D(k) is predicted to be p-wave, i.e., l = 1, S = 1, as compared to l = 2 and S = 1 for conventional HTS materials. In addition a novel collective model is predicted whose frequency, wL is in the optical range and is determined by Hsdp.